2005
DOI: 10.1111/j.1471-4159.2005.03256.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing the infiltrating character of brain tumors: inhibition of RhoA/ROK‐mediated CD44 cell surface shedding from glioma cells by the green tea catechin EGCg

Abstract: Glioma cell-surface binding to hyaluronan (HA), a major constituent of the brain extracellular matrix (ECM) environment, is regulated through a complex membrane type-1 matrix metalloproteinase (MT1-MMP)/CD44/caveolin interaction that takes place at the leading edges of invading cells. In the present study, intracellular transduction pathways required for the HA-mediated recognition by infiltrating glioma cells in brain was investigated. We show that the overexpression of the GTPase RhoA up-regulated MT1-MMP ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 53 publications
3
54
0
Order By: Relevance
“…Moreover, in line with the CD133(+) tumor cell phenotype that accounts for glioma stem cells' radioresistance (13), the expression of MT1-MMP expression was also increased in several cell line models that escaped radiationinduced apoptosis (14,15). Previous reports from our laboratory have documented the contribution of MT1-MMP to the infiltrative and invasive phenotype of brain tumorderived cells (16,17), and strategies which inhibit either MMP-9 or MT1-MMP activities and/or expression may, furthermore, be envisioned to reduce tumorigenicity (17)(18)(19). Whether expression of MMP-9 or MT1-MMP affects the acquisition of an invasive phenotype during neurosphere-like formation of CSC is currently unknown.…”
Section: Introductionmentioning
confidence: 74%
“…Moreover, in line with the CD133(+) tumor cell phenotype that accounts for glioma stem cells' radioresistance (13), the expression of MT1-MMP expression was also increased in several cell line models that escaped radiationinduced apoptosis (14,15). Previous reports from our laboratory have documented the contribution of MT1-MMP to the infiltrative and invasive phenotype of brain tumorderived cells (16,17), and strategies which inhibit either MMP-9 or MT1-MMP activities and/or expression may, furthermore, be envisioned to reduce tumorigenicity (17)(18)(19). Whether expression of MMP-9 or MT1-MMP affects the acquisition of an invasive phenotype during neurosphere-like formation of CSC is currently unknown.…”
Section: Introductionmentioning
confidence: 74%
“…The subtype of medulloblastoma characterized by OTX2 overexpression and extensive chromatin modifications has recently been shown to be responsive to all trans retinoic acid-induced apoptosis (Acampora et al, 2005) whereas nodular/desmoplastic tumor types, which do not overexpress OTX2, are not responsive. In the Daoy cell line, CD44, CAV 1 and 2, EGFR and several MAGE genes were overexpressed and contained high H3K9Me3 levels compared with D283; all these genes have been considered potential therapeutic targets (Chomez et al, 2001;Annabi et al, 2005;Arslan et al, 2006;Jin et al, 2006;Tijink et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…CD44 receptor is overexpressed in glioma cells in vitro (Wiranowska et al 2000, Yu et al 2010) and found in vivo at the leading edge of glioma at the brain-tumor interface (Wiranowska et al 2006). The HA-CD44 interaction and CD44 shedding from the cell surface were found to be associated with glioma cell motility, migration, and infiltration into the normal brain parenchyma (Annabi et al 2005). These authors also described that CD44 shedding was mediated by HA and accompanied by up-regulation of MT1-MMP expression.…”
Section: Extracellular Matrix Molecules In Glioma 341 Glycosaminoglmentioning
confidence: 99%